2018
DOI: 10.1089/acm.2018.0195
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Penny Brohn UK's Living Well Course on Informal Caregivers of People with Cancer

Abstract: Objectives: This study evaluated the change in the concerns, wellbeing and lifestyle behaviours of informal caregivers of people with cancer attending Penny Brohn UK's Living Well Course (LWC), a self-management education intervention. Design: A pre-post-course design collected self-reported quantitative and qualitative data from informal caregivers attending a LWC. Setting/Location: Penny Brohn UK is a UK based charity (not-for-profit) providing specialist integrative, whole person support, free of charge, to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Post-traumatic growth refers to a feeling of growth experienced by the person as a result of a traumatic experience (i.e. cancer of a loved one), expressed through changes to the person’s self-perception, relationship with others and life philosophy (Tedeschi and and Calhoun, 1996) and self-compassion refers to the ability to treat oneself with kindness and acceptance when going through difficult life events (Neff and Dahm, 2015) Finally, well-being is a multidimensional term including emotional, physical and spiritual aspects, such as having one’s own and their loved one’s emotional needs addressed, having adequate nutrition and exercise habits, and finding a meaning in life (Jolliffe et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Post-traumatic growth refers to a feeling of growth experienced by the person as a result of a traumatic experience (i.e. cancer of a loved one), expressed through changes to the person’s self-perception, relationship with others and life philosophy (Tedeschi and and Calhoun, 1996) and self-compassion refers to the ability to treat oneself with kindness and acceptance when going through difficult life events (Neff and Dahm, 2015) Finally, well-being is a multidimensional term including emotional, physical and spiritual aspects, such as having one’s own and their loved one’s emotional needs addressed, having adequate nutrition and exercise habits, and finding a meaning in life (Jolliffe et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Limited qualitative research has shown that patients with advanced lung cancer and their family caregivers include complementary and alternative medicine among the main strategies being used for coping with their illness, 11 and that informal caregivers are interested in obtaining reliable information on lifestyle changes, including stress management, proper nutrition and relaxation techniques, for both the patient and for themselves. 12…”
Section: Introductionmentioning
confidence: 99%
“…Limited qualitative research has shown that patients with advanced lung cancer and their family caregivers include complementary and alternative medicine among the main strategies being used for coping with their illness, 11 and that informal caregivers are interested in obtaining reliable information on lifestyle changes, including stress management, proper nutrition and relaxation techniques, for both the patient and for themselves. 12 Many cancer centers offer Integrative Oncology services, in which non-conventional medical therapies are provided within the center's supportive and palliative cancer care setting. 13,14 These services are headed by medical doctors with training and experience in CM and who integrate these practices in their therapeutic repertoire, and are commonly referred to as "integrative physicians" (IPs).…”
Section: Introductionmentioning
confidence: 99%